Seeing the Light: The Use of Zebrafish for Optogenetic Studies of the Heart - Baillie, Jonathan S.; Stoyek, Matthew R.; Quinn, T. Alexander (Frontiers in Physiology, 2021)
Optogenetics, involving the optical measurement and manipulation of cellular activity with genetically encoded light-sensitive proteins (‘reporters’ and ‘actuators’), is a powerful experimental technique for probing (patho-)physiological function. Originally developed as a tool for neuroscience, it has now been utilised in cardiac research for over a decade, providing novel insight into the electrophysiology of the healthy and diseased heart. Among the pioneering cardiac applications of optogenetic actuators were studies in zebrafish, which first demonstrated their use for precise spatiotemporal control of cardiac activity. Zebrafish were also adopted early as an experimental model for the use of optogenetic reporters, including genetically encoded voltage- and calcium-sensitive indicators. Beyond optogenetic studies, zebrafish are becoming an increasingly important tool for cardiac research, as they combine many of the advantages of integrative and reduced experimental models. The zebrafish has striking genetic and functional cardiac similarities to that of mammals, its genome is fully sequenced and can be modified using standard techniques, it has been used to recapitulate a variety of cardiac diseases, and it allows for high-throughput investigations. For optogenetic studies, zebrafish provide additional advantages, as the whole zebrafish heart can be visualised and interrogated in vivo in the transparent, externally developing embryo, and the relatively small adult heart allows for in situ cell-specific observation and control not possible in mammals. With the advent of increasingly sophisticated fluorescence imaging approaches and methods for spatially-resolved light stimulation in the heart, the zebrafish represents an experimental model with unrealised potential for cardiac optogenetic studies. In this review we summarise the use of zebrafish for optogenetic investigations in the heart, highlighting their specific advantages and limitations, and their potential for future cardiac research.